Quo virtus? - DeWitt, H; DeWitt, H. M. (1987)
The standard of propriety is frequently appealed to in ancient literary discourse, most notably in discussions of poetics, criticism of literary works and precepts for composition. Its importance derives from the audience orientation of most ancient discussions of literature: writers were interested in the ways various forms of speech and writing had to be accommodated to their audience in order to achieve particular effects. Discussion of the representation of character, for instance, explored the ways that fictional persons or oratorical speakers could be made moving and convincing: they must conform to common preconceptions about the behviour and language suitable to their rank, sex, age, nationality, education. This raises important questions about the concept of propriety. First, is it coherent? It seems to depend heavily on the assumption that audiences are homogeneous; in practice, however, ancient writers recognise wide disparities in readers and spectators, and are often ready to accuse certain types of audience of bad taste. The concept is thus embroiled in the general aesthetic problem of the nature of taste: can criteria for artistic excellence be found which are independent of what people happen to like, and which can therefore justify claims about what they should like? Second, where does use of the concept place ancient literary discussion in relation to various forms of modern literary theory and criticism? A large number of modern movements have held it as axiomatic that the excellence of art lies in defeating the preconceptions of the audience; does ancient criticism have any defence against such a position? Both of these points touch on further issues: the place of literature and oratory in Greek and Roman societies, and the connection between literary discourse and other types of intellectual activity, most notably philosophy (propriety is equally important in most ancient moral philosophy). I consider these points in connection with major poetic genres, rhetoric, and the question of linguistic purity.